Thin Client System for Education Purpose using Raspberry Pi - Handayani, Rini; Siregar, Simon; Ike Sari, Marlindia; Afrizal, Gaous (International Journal of Engineering and Technology, 2018)
Procurement of computers for infrastructure that supports learning in schools requires a lot of money. The application of the Computer Thin Client system can be an alternative solution to these problems. The use of thin client computers, can reduce resource use, so that it can make costs more efficient. The use of single board computers, is also a cost efficiency, as a substitute for computers. This system consists of one server and several single board computers as thin clients. In a Computer Thin Client network, the server has a very important role that functions as a processor and serves the activities of the client that performs the input / output process. This system also features a monitoring function to monitor the performance of resources from servers and client activities. In this study, the processes carried out by the development of server and client system infrastructure, build LTSP for the formation of thin clients and resource sharing, as well as the development of monitoring systems.Â